2001
DOI: 10.1073/pnas.071411598
|View full text |Cite
|
Sign up to set email alerts
|

Tumor metastasis suppressor nm23H1 regulates Rac1 GTPase by interaction with Tiam1

Abstract: The putative tumor metastasis suppressor nm23H1 was originally identified in murine melanomas by subtraction cloning. It displays nucleoside diphosphate kinase activity and regulates cellular events, including growth and development. Recently nm23H1 has been reported to also act as a GTPase-activating protein of the Ras-related GTPase Rad. We attempted to determine whether nm23H1 also regulates Rho-family GTPases. Although we were unable to detect a direct association between nm23H1 and Rhofamily GTPases, nm23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 44 publications
(58 reference statements)
4
140
2
1
Order By: Relevance
“…Paradoxalement, il s'agit d'une inhibition, en accord avec le rôle de suppresseur de métastases. L'interaction de NM23-H1 avec Tiam1, facteur d'échange nucléotidique de Rac1, Rho-GTPase impliquée dans la motilité cellulaire, inhibe l'activation de Rac1 [10]. NM23-H1, en interagissant avec la protéine d'échaffaudage KSR, inhibe l'activation de la voie ERK/MAPK [11].…”
Section: Nm23unclassified
“…Paradoxalement, il s'agit d'une inhibition, en accord avec le rôle de suppresseur de métastases. L'interaction de NM23-H1 avec Tiam1, facteur d'échange nucléotidique de Rac1, Rho-GTPase impliquée dans la motilité cellulaire, inhibe l'activation de Rac1 [10]. NM23-H1, en interagissant avec la protéine d'échaffaudage KSR, inhibe l'activation de la voie ERK/MAPK [11].…”
Section: Nm23unclassified
“…The nm23 proteins have been reported to possess both a histidine protein kinase activity and a phosphotransferase activity; the latter potentially represents an additional mechanism by which the nm23s can influence the metastasis and differentiation processes (MacDonald et al, 1996;Wagner et al, 1997). To date, several nm23 interactors have been described in mammals, including Rad, Tiam1, Arf6, the nucleosome assembly protein SET, Cdc42, EBNA1 and KSR (Otsuki et al, 2001;Tseng et al, 2001;Palacios et al, 2002), although their roles are not fully understood. AMPKa1, a heterotrimeric kinase that is a sensor of cellular energy status, binds to and phosphorylates nm23-H1, which in turn channels the ATP produced by its enzymatic activity to AMP activated kinase (AMPK) (Crawford et al, 2005(Crawford et al, , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the nm23H1 gene plays a major role in metastasis and its mechanism of suppressing metastasis may involve downregulation of nm23H1 and inhibition of ovarian cancer metastasis J Li et al genes associated with cell adhesion and motility (integrins alpha2, -8, -9, -L, and -V, collagen type VIII alpha1, fibronectin 1, catenin, TGF-beta2, FGF7, MMP14 and 16, ErbB2), and possibly certain tumor/metastasis suppressors (two members of SWI/SNF-related matrix-associated proteins 2 and 5, and PTEN). 2,8,38 Moreover, nm23H1 may negatively regulate Tiam1 and inhibit Rac1 activation in vivo. Its regulation of Rac1 implicated nm23H1 in the suppression of tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%